Depression and Dementia: The Role of Cortisol and Vascular Brain Lesions. AGES-Reykjavik Study. - Gerritsen, Lotte; Twait, Emma L; Jonsson, Palmi V; Gudnason, Vilmundur; Launer, Lenore J; Geerlings, Mirjam I (J Alzheimers Dis, 2021)
BACKGROUND: Late-life depression (LLD) is related to an increased risk of developing dementia; however, the biological mechanisms explaining this relationship remain unclear. OBJECTIVE: To determine whether the relationship between LLD and dementia can be best explained by the glucocorticoid cascade or vascular hypothesis. METHODS: Data are from 4,354 persons (mean age 76±5 years) without dementia at baseline from the AGES-Reykjavik Study. LLD was assessed with the MINI diagnostic interview (current and remitted major depressive disorder [MDD]) and the Geriatric Depression Scale-15. Morning and evening salivary cortisol were collected (glucocorticoid cascade hypothesis). White matter hyperintensities (WMH; vascular hypothesis) volume was assessed using 1.5T brain MRI. Using Cox proportional hazard models, we estimated the associations of LLD, cortisol levels, and WMH volume with incident all-cause dementia, AD, and non-AD dementia. RESULTS: During 8.8±3.2 years of follow-up, 843 persons developed dementia, including 397 with AD. Current MDD was associated with an increased risk of developing all-cause dementia (HR = 2.17; 95% CI 1.66-2.67), with risks similar for AD and non-AD, while remitted MDD was not (HR = 1.02; 95% CI 0.55-1.49). Depressive symptoms were also associated with increased risk of dementia, in particular non-AD dementias. Higher levels of evening cortisol increased risk of dementia, but this was independent of MDD. WMH partially explained the relation between current MDD and dementia risk but remained increased (HR = 1.71; 95% CI 1.34-2.08). CONCLUSION: The current study highlights the importance of LLD in developing dementia. However, neither the glucocorticoid cascade nor the vascular hypotheses fully explained the relation between depression and dementia.

Automated Multi-Atlas Segmentation of Hippocampal and Extrahippocampal Subregions in Alzheimer's Disease at 3T and 7T: What Atlas Composition Works Best? - Xie, Long; Shinohara, Russell T; Ittyerah, Ranjit; Kuijf, Hugo J; Pluta, John B; Blom, Kim; Kooistra, Minke; Reijmer, Yael D; Koek, Huiberdina L; Zwanenburg, Jaco J M; Wang, Hongzhi; Luijten, Peter R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Multi-atlas segmentation, a popular technique implemented in the Automated Segmentation of Hippocampal Subfields (ASHS) software, utilizes multiple expert-labelled images ("atlases") to delineate medial temporal lobe substructures. This multi-atlas method is increasingly being employed in early Alzheimer's disease (AD) research, it is therefore becoming important to know how the construction of the atlas set in terms of proportions of controls and patients with mild cognitive impairment (MCI) and/or AD affects segmentation accuracy. OBJECTIVE: To evaluate whether the proportion of controls in the training sets affects the segmentation accuracy of both controls and patients with MCI and/or early AD at 3T and 7T. METHODS: We performed cross-validation experiments varying the proportion of control subjects in the training set, ranging from a patient-only to a control-only set. Segmentation accuracy of the test set was evaluated by the Dice similarity coeffiecient (DSC). A two-stage statistical analysis was applied to determine whether atlas composition is linked to segmentation accuracy in control subjects and patients, for 3T and 7T. RESULTS: The different atlas compositions did not significantly affect segmentation accuracy at 3T and for patients at 7T. For controls at 7T, including more control subjects in the training set significantly improves the segmentation accuracy, but only marginally, with the maximum of 0.0003 DSC improvement per percent increment of control subject in the training set. CONCLUSION: ASHS is robust in this study, and the results indicate that future studies investigating hippocampal subfields in early AD populations can be flexible in the selection of their atlas compositions.

White Matter Hyperintensities and Cognition in Mild Cognitive Impairment and Alzheimer's Disease: A Domain-Specific Meta-Analysis. - van den Berg, Esther; Geerlings, Mirjam I; Biessels, Geert Jan; Nederkoorn, Paul J; Kloppenborg, Raoul P (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMHs) are related to cognitive dysfunction in the general population. The clinical relevance of WMHs in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) is, however, unclear. OBJECTIVE: This meta-analysis aimed to quantify the association of WMHs and specific cognitive domains in patients with MCI or AD. METHODS: PubMed (January 1990-January 2017) was searched for studies that used MRI to quantify WMHs, and measured cognitive functioning (≥1 predefined cognitive domain with ≥1 test) in a well-defined population of persons diagnosed with MCI or AD. Fischer's Z was used as the common metric for effect size. Modifying effects of demographics, MMSE, and WMH location were examined. RESULTS: Twelve cross-sectional studies on AD (total n = 1,370, median age 75 years) and 10 studies on MCI (9 cross-sectional, 1 longitudinal; total n = 2,286, median age 73 years) were included. The association between WMHs and overall cognition was significantly stronger for MCI (-0.25, -0.36 to -0.14) than for AD (-0.11, -0.14 to -0.08; QM = 10.7, p < 0.05). For both groups, largest effect sizes were found in attention and executive functions (-0.26, -0.36 to -0.15) and processing speed (-0.21, -0.35 to -0.12). No significant modifying effects of age and gender were found. CONCLUSION: WMHs have a medium-sized association with different cognitive functions in patients with MCI and a small, but statistically significant, association with cognition in AD. These result underscore the role of co-occurring vascular brain damage in MCI and AD.